O teatro de Deus: a construção do espaço sagrado de Juazeiro a partir de narrativas femininas (Ceará, 1889-1898) - Nobre, Edianne dos Santos (2010)
In this work, we discuss the construction of Juazeiro in the state of Ceará -, as a sacred space from the analysis of the testimonies of nine religious women called beatas in an Episcopal process in the late nineteenth century. This process was initiated in 1891 to investigate the occurrence of an Eucharistic miracle with beata Maria Magdalena do Espírito Santo de Araújo. We show that the punitive strategies of the Diocese eventually caused a reordering of pilgrimages to Juazeiro which until 1894 worshipped the Precious Blood and that after the condemnation of the phenomena by the Holy See are rearranged around the figure of Father Cicero Romão Batista, under the pretext of worshipping the priest himself and also Nossa Senhora das Dores, currently the patron saint of the city of Juazeiro do Norte.